Brine chemical equipment with anti-corrosion function
By preparing anti -corrosion coating in the inner wall system of brine chemical equipment, the problem of difficulty comprehensively cleaning in the inner wall of the equipment is solved, and the efficient corrosion resistance and ultra -hydrophobic performance of the equipment are realized. Essence
Patent Information
- Application Number
- CN202411271523.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-11
- Publication Date
- 2025-01-28
AI Technical Summary
The inner wall of brine chemical equipment is difficult to clean in full during cleaning, which is prone to scaling or corrosion damage, affecting the normal operation of the equipment.
Inner wall system of brine chemical equipment prepare anti -corrosion coating, to form coatings through the steps of pouring the grassroots, electrostatic spinning composite film, and spraying anti -corrosion coating. This coating is prepared by a specific raw material, including bisphenol A two -shrimply gly gly gly gly gly gly gly glycerin, neosterophenol diodeceride ether, tough agent and curing agent, polyester particles and epoxy resin in static spinning solution, and epoxy resin, and Metropolitan soil and silicon carbide.
Effectively prevent the corrosion and scaling of the inner wall of the brine chemical equipment, improve the corrosion resistance and ultra -hydrophobic performance of the equipment, and the coating has a self -repair function, which can maintain long -term performance in the cleaning operation.
Smart Images

Figure BDA0005038855300000071 
Figure BDA0005038855300000081
Abstract
Description
Technical Field
[0001] The present invention relates to the field of anti-corrosion technology, and more specifically, to brine chemical equipment with anti-corrosion function. Background Art
[0002] Brine chemical industry mainly involves the production and processing of brine to prepare salts and their by-products; the scientific name of brine is bittern, which is a mixture of magnesium chloride, magnesium sulfate and sodium chloride; according to the water chemical properties of brine, it is divided into chloride brine, sulfate brine and carbonate brine. The steps of brine salt production include: raw materials → purification → evaporation and crystallization → separation → drying → product, among which the main steps are purification and evaporation.
[0003] During the purification process, since the brine contains impurities such as calcium, magnesium, and sulfate, scaling (magnesium sulfate, calcium sulfate, etc.) will occur during evaporation, affecting the evaporation efficiency, increasing energy consumption, and more seriously clogging the pipeline, causing the process to be unable to proceed normally. Therefore, brine salt production needs to be purified first, and the main equipment for purification includes reaction barrels, agitators, clarification barrels, etc.; Evaporation process: The main equipment for vacuum tube evaporation salt production is the evaporation tank, which consists of a heating chamber and an evaporation chamber. At present, vacuum multi-effect evaporation generally adopts a four-effect or five-effect evaporation process, and its main equipment includes a preheater, an evaporation tank, a circulation pump, a salt output system, a vacuum system, a cooling system, a separator, and a dryer. Due to the particularity of brine salt production, equipment often needs to be cleaned during the production and processing process, especially the inner wall of the equipment that is in direct contact with brine or crystals needs to be cleaned more.
[0004] However, it is difficult to ensure the comprehensive cleaning of the inner wall of the brine salt-making equipment, and these cleaning dead corners are prone to scaling or corrosion damage. Summary of the invention
[0005] In order to overcome the above-mentioned defects of the prior art, an embodiment of the present invention provides a brine chemical equipment with anti-corrosion function.
[0006] A brine chemical equipment with anti-corrosion function, wherein an anti-corrosion coating is made on the inner wall of the brine chemical equipment, and the specific preparation steps are as follows:
[0007] Step 1: pour and solidify the base layer on the inner wall surface of the brine chemical equipment;
[0008] Step 2: electrospinning a composite membrane on the surface of a substrate by electrospinning a solution;
[0009] Step 3: spray the spray liquid on the surface of the composite film, solidify it, and produce an anti-corrosion coating.
[0010] Furthermore, the raw materials of the base layer include bisphenol A diglycidyl ether, neopentyl glycol diglycidyl ether, a toughening agent and a curing agent A, and the weight ratio of the bisphenol A diglycidyl ether, neopentyl glycol diglycidyl ether, the toughening agent and the curing agent A is 1: (0.09-0.11): (0.13-0.17): (0.2-0.3).
[0011] Furthermore, the raw materials of the electrospinning solution include polycaprolactone particles, N,N-dimethylformamide and dichloromethane, the volume ratio of N,N-dimethylformamide to dichloromethane is (2.8-3.2):1, and the mass fraction of polycaprolactone particles in the electrospinning solution is 15.5-16.5%.
[0012] Furthermore, the raw materials included in the spray liquid include diatomaceous earth, tetraethyl silicate, octadecyltrimethoxysilane, silicon carbide, perfluorooctyltriethoxysilane, epoxy resin and curing agent B; the weight ratio of diatomaceous earth, tetraethyl silicate, octadecyltrimethoxysilane, silicon carbide and perfluorooctyltriethoxysilane is 1:(0.8-1.0):(0.6-0.7):(0.6-0.7):(0.1-0.2); the weight ratio of the total weight of diatomaceous earth and silicon carbide to the epoxy resin is 1:(3.5-4.5); the weight ratio of epoxy resin and curing agent B is 1:(0.2-0.3).
[0013] Furthermore, the weight ratio of bisphenol A diglycidyl ether, neopentyl glycol diglycidyl ether, toughening agent and curing agent A is 1:0.1:0.15:0.25; the volume ratio of N,N-dimethylformamide and dichloromethane is 3.0:1, and the mass fraction of polycaprolactone particles in the electrospinning solution is 16.0%; the weight ratio of diatomaceous earth, tetraethyl silicate, octadecyltrimethoxysilane, silicon carbide and perfluorooctyltriethoxysilane is 1:0.9:0.65:0.65:0.15; the weight ratio of the total weight of diatomaceous earth and silicon carbide to epoxy resin is 1:4.0; the weight ratio of epoxy resin and curing agent B is 1:0.25.
[0014] Furthermore, the toughening agent is one or more of n-octylamine, n-nonylamine, n-decylamine, n-dodecylamine and n-hexadecylamine; the curing agent A and curing agent B are one or more of ethylenediamine, hexamethylenediamine, diethylenetriamine, triethylenetetramine, diethylaminopropylamine, polyetheramine and m-xylylenediamine.
[0015] Furthermore, in step one, the bisphenol A diglycidyl ether, neopentyl glycol diglycidyl ether, toughening agent and curing agent A in the base raw materials are mixed and stirred evenly, and then poured on the inner wall surface of the brine chemical equipment for curing treatment to prepare the base; during the curing process, it is first cured at 55-65°C for 0.5-1.5 hours, and then cured at 90-100°C for 1-2 hours.
[0016] Furthermore, in step 2, the polycaprolactone particles in the electrospinning liquid raw material are dissolved in N, N-dimethylformamide and dichloromethane to obtain an electrospinning liquid; the electrospinning liquid is electrospun on the surface of the base layer, and dried to produce a composite film; the electrospinning parameters are: voltage 13-17KV, receiving distance 12-18cm, spinning liquid flow rate 1.1-1.5ml / h; after electrospinning, it is dried at 40-50°C for 11-13h.
[0017] Further, in step three, diatomaceous earth and silicon carbide in the coating liquid are added to anhydrous ethanol and ultrasonically treated for 10 to 20 minutes, and then tetraethyl silicate, octadecyl trimethoxysilane and perfluorooctyl triethoxysilane are added, stirred in a water bath for 11 to 13 hours, centrifuged, filtered, and dried to obtain super-hydrophobic modified particles; super-hydrophobic modified particles, epoxy resin and curing agent B are added to anhydrous ethanol, ultrasonically treated for 30 to 60 minutes to obtain a spray liquid, and the spray liquid is sprayed on the composite The membrane surface is cured to produce an anti-corrosion coating; the weight ratio of the total weight of diatomaceous earth and silicon carbide to anhydrous ethanol is 1:20-30, the water bath temperature is 40-50°C, and the stirring speed is 300-500r / min; the weight ratio of the epoxy resin to anhydrous ethanol is 1:4-6, the ultrasonic frequency is 1.5-1.7MHz, and the ultrasonic power is 400-600W; the spraying pressure is 0.15-0.25MPa, and the curing treatment is carried out at 55-65°C for 3-5 hours.
[0018] Furthermore, in step one, during the curing process, the curing is first carried out at 60°C for 1.0 hour, and then at 95°C for 1.5 hours; in step two, the electrospinning parameters are: voltage 15KV, receiving distance 15cm, spinning solution flow rate 1.3ml / h; after electrospinning, it is dried at 45°C for 12h; in step three, the weight ratio of the total weight of diatomaceous earth and silicon carbide to anhydrous ethanol is 1:25, the water bath temperature is 45°C, and the stirring speed is 400r / min; the weight ratio of the epoxy resin to anhydrous ethanol is 1:5, the ultrasonic frequency is 1.6MHz, and the ultrasonic power is 500W; the spraying pressure is 0.20MPa, and the curing treatment is carried out at 60°C for 4 hours.
[0019] Technical effects and advantages of the present invention:
[0020] 1. The brine chemical equipment with anti-corrosion function prepared by the raw material formula of the present invention is coated with an anti-corrosion coating on the inner wall of the brine chemical equipment, which can effectively carry out anti-corrosion treatment on the inner wall of the brine chemical equipment. At the same time, the super-hydrophobic property of the anti-corrosion coating can effectively prevent the brine from hanging on the inner wall of the brine chemical equipment during the processing, thereby further improving the anti-corrosion performance of the brine chemical equipment. At the same time, the anti-corrosion coating can be self-repaired, and the anti-corrosion coating will not be damaged due to cleaning operation, thereby effectively ensuring the long-term effectiveness of the anti-corrosion and super-hydrophobic properties of the brine chemical equipment. Due to the super-hydrophobic property of the anti-corrosion coating, the cleaning effect of the inner wall of the brine chemical equipment can be effectively improved to avoid scaling and corrosion damage. The composite film with self-repairing function is prepared by combining polycaprolactone nanofibers with epoxy-based shape memory polymer resins through electrospinning technology, and its thermoplastic characteristics can be used to impart The super-hydrophobic coating has the function of self-repair; the super-hydrophobic coating has excellent wear resistance; the coating has excellent anti-corrosion performance and has long-lasting corrosion resistance; the coating has good self-repairability, and the coating still shows excellent corrosion resistance after repair; after heat treatment, the composite membrane with self-repairing function regains the flow state due to thermoplasticity, and the cracks at the damaged part can be repaired. When the temperature drops, the coating solidifies again, and the low surface energy of the repaired coating surface is not destroyed. At the same time, the micro-nano structure is restored. At this time, the rolling angle of the self-repaired coating surface is restored, and the super-hydrophobicity of the coating is repaired; the surface of the polycaprolactone nanofiber membrane has abundant hydroxyl groups, which can chemically bond with the epoxy groups in the upper epoxy resin, so that the modified diatomaceous earth particles and silicon carbide can be firmly attached to the surface of the fiber membrane, thereby significantly improving the wear resistance and bonding strength of the particles;
[0021] 2. In the present invention, bisphenol A diglycidyl ether, neopentyl glycol diglycidyl ether, toughening agent and curing agent A in the base material are mixed and stirred evenly, and then poured and cured to prepare an epoxy shape memory polymer (SMP) on the inner wall surface of the brine chemical equipment to provide a supporting matrix for subsequent electrospinning fibers and ensure the self-repairing function of the composite membrane; polycaprolactone particles are dissolved in N, N-dimethylformamide and dichloromethane to prepare an electrospinning solution, and the electrospinning solution is electrospun on the surface of the epoxy shape memory polymer (SMP) to obtain a composite membrane with self-repairing function; octadecyl trimethoxy silane and perfluorooctyl triethoxy silane are used to treat the surfaces of diatomaceous earth and silicon carbide After modification, the -OH groups on the oligosiloxane react with the hydroxyl groups adsorbed on the surface of silicon carbide to form hydrogen bonds. These hydrogen bonds are dehydrated during heating to form Si-O-Si covalent bonds with silicon carbide. The Si-O-Si covalent bonds effectively promote the adhesion between the epoxy resin and the silicon carbide particles, forming a tight chemical interface layer to prevent the infiltration of water molecules, further improving the superhydrophobic properties of the coating; the superhydrophobic modified particles, epoxy resin and m-phenylenediamine are added to anhydrous ethanol for blending, spraying, and curing to produce an anti-corrosion coating. The addition of epoxy resin can fix the superhydrophobic modified particles well on the surface of the composite film. At the same time, the introduction of epoxy resin further improves the overall mechanical strength of the anti-corrosion coating. DETAILED DESCRIPTION
[0022] The following will be described clearly and completely in conjunction with the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0023] Embodiment 1:
[0024] The present invention provides a brine chemical equipment with anti-corrosion function, and an anti-corrosion coating is prepared on the inner wall of the brine chemical equipment. The specific preparation steps are as follows:
[0025] Step 1: bisphenol A diglycidyl ether, neopentyl glycol diglycidyl ether, n-decylamine and m-xylylenediamine in the base raw materials are mixed and stirred evenly according to a weight ratio of 1:0.09:0.13:0.2, and then poured on the inner wall surface of the brine chemical equipment for curing treatment (first curing at 55°C for 0.5 hour, and then curing at 90°C for 1 hour) to prepare a base;
[0026] Step 2: dissolving the polycaprolactone particles in the electrospinning solution raw material in N, N-dimethylformamide and dichloromethane to prepare an electrospinning solution (the volume ratio of N, N-dimethylformamide and dichloromethane is 2.8:1, and the mass fraction of polycaprolactone particles in the electrospinning solution is 15.5%); electrospinning the electrospinning solution on the surface of the substrate, and drying it to prepare a composite film; electrospinning parameters: voltage 13KV, receiving distance 12cm, spinning solution flow rate 1.1ml / h; drying at 40°C for 11h after electrospinning;
[0027] Step 3: Add diatomaceous earth and silicon carbide in the coating liquid to anhydrous ethanol for ultrasonic treatment for 15 minutes, the weight ratio of the total weight of diatomaceous earth and silicon carbide to anhydrous ethanol is 1:20, then add tetraethyl silicate, octadecyl trimethoxysilane and perfluorooctyl triethoxysilane, stir in a water bath for 12 hours, the water bath temperature is 40°C, the stirring speed is 300r / min, centrifuge, filter, and dry to obtain super hydrophobic modified particles (the weight ratio of diatomaceous earth, tetraethyl silicate, octadecyl trimethoxysilane, silicon carbide, and perfluorooctyl triethoxysilane is 1:0.8:0.6:0.6:0 .1); add super-hydrophobic modified particles, epoxy resin and meta-xylenediamine into anhydrous ethanol, the weight ratio of the total weight of diatomaceous earth and silicon carbide to the weight ratio of epoxy resin is 1:3.5, the weight ratio of the epoxy resin to anhydrous ethanol is 1:4, and the weight ratio of epoxy resin to meta-xylenediamine is 1:0.2, ultrasonic treatment for 45 minutes, the ultrasonic frequency is 1.5MHz, the ultrasonic power is 400W, and a spray liquid is obtained, the spray liquid is sprayed on the surface of the composite membrane, and cured to produce an anti-corrosion coating (coating thickness is 80±5μm); the spraying pressure is 0.15MPa, and the curing treatment is carried out at 55℃ for 3 hours.
[0028] Embodiment 2:
[0029] Different from Example 1, the weight ratio of bisphenol A diglycidyl ether, neopentyl glycol diglycidyl ether, toughening agent and curing agent A is 1:0.11:0.17:0.3; the volume ratio of N,N-dimethylformamide and dichloromethane is 3.2:1, and the mass fraction of polycaprolactone particles in the electrospinning solution is 16.5%; the weight ratio of diatomaceous earth, tetraethyl silicate, octadecyltrimethoxysilane, silicon carbide and perfluorooctyltriethoxysilane is 1:1.0:0.7:0.7:0.2; the weight ratio of the total weight of diatomaceous earth and silicon carbide to epoxy resin is 1:4.5; the weight ratio of epoxy resin and curing agent B is 1:0.3.
[0030] Embodiment 3:
[0031] Different from Examples 1-2, the weight ratio of bisphenol A diglycidyl ether, neopentyl glycol diglycidyl ether, toughening agent and curing agent A is 1:0.1:0.15:0.25; the volume ratio of N,N-dimethylformamide and dichloromethane is 3.0:1, and the mass fraction of polycaprolactone particles in the electrospinning solution is 16.0%; the weight ratio of diatomaceous earth, tetraethyl silicate, octadecyltrimethoxysilane, silicon carbide and perfluorooctyltriethoxysilane is 1:0.9:0.65:0.65:0.15; the weight ratio of the total weight of diatomaceous earth and silicon carbide to epoxy resin is 1:4.0; the weight ratio of epoxy resin and curing agent B is 1:0.25.
[0032] Embodiment 4:
[0033] Different from Example 3, in step one, during the curing process, the curing is first carried out at 60°C for 1.0 hour, and then at 95°C for 1.5 hours; in step two, the electrospinning parameters are: voltage 15KV, receiving distance 15cm, spinning solution flow rate 1.3ml / h; after electrospinning, it is dried at 45°C for 12h; in step three, the weight ratio of the total weight of diatomaceous earth and silicon carbide to anhydrous ethanol is 1:25, the water bath temperature is 45°C, and the stirring speed is 400r / min; the weight ratio of the epoxy resin to anhydrous ethanol is 1:5, the ultrasonic frequency is 1.6MHz, and the ultrasonic power is 500W; the spraying pressure is 0.20MPa, and the curing treatment is carried out at 60°C for 4 hours.
[0034] Comparative Example 1:
[0035] The difference from Example 4 is that: an epoxy resin coating is formed on the inner wall surface of the brine chemical equipment;
[0036] Preparation of epoxy resin coating: Take epoxy resin, m-phenylenediamine and anhydrous ethanol (weight ratio of 1:0.25:5), stir evenly and spray on the inner wall surface of brine chemical equipment, place it at room temperature to cure, and obtain epoxy resin coating for comparison. The coating thickness is 80μm.
[0037] Comparative Example 2:
[0038] The difference from Example 4 is that an anti-corrosion coating is prepared on the inner wall of the brine chemical equipment, and the specific preparation steps are as follows:
[0039] Step 1: bisphenol A diglycidyl ether, neopentyl glycol diglycidyl ether, n-decylamine and m-xylylenediamine in the base raw materials are mixed and stirred evenly according to a weight ratio of 1:0.1:0.15:0.25, and then poured on the inner wall surface of the brine chemical equipment for curing treatment (first curing at 60°C for 1.0 hour, and then curing at 95°C for 1.5 hours) to prepare a base;
[0040] Step 2: dissolving the polycaprolactone particles in the electrospinning solution raw material in N, N-dimethylformamide and dichloromethane to prepare an electrospinning solution (the volume ratio of N, N-dimethylformamide and dichloromethane is 3:1, and the mass fraction of polycaprolactone particles in the electrospinning solution is 16.0%); electrospinning the electrospinning solution on the surface of the substrate, and drying it to prepare a composite film; electrospinning parameters: voltage 15KV, receiving distance 15cm, spinning solution flow rate 1.3ml / h; drying at 45°C for 12h after electrospinning;
[0041] Step 3: adding diatomaceous earth in the coating liquid to anhydrous ethanol for ultrasonic treatment for 15 minutes, the weight ratio of diatomaceous earth to anhydrous ethanol is 1:20, then adding tetraethyl silicate and octadecyltrimethoxysilane, stirring in a water bath for 12 hours, the water bath temperature is 40°C, the stirring speed is 300r / min, centrifuging, filtering, and drying to obtain super hydrophobic modified particles (the weight ratio of diatomaceous earth, tetraethyl silicate, and octadecyltrimethoxysilane is 1:0.9:0.65); super hydrophobic modified particles, epoxy resin and Meta-phenylenediamine is added to anhydrous ethanol, the weight ratio of the diatomaceous earth to the epoxy resin is 1:4.0, the weight ratio of the epoxy resin to anhydrous ethanol is 1:4, and the weight ratio of the epoxy resin to meta-phenylenediamine is 1:0.2. Ultrasonic treatment is carried out for 45 minutes, the ultrasonic frequency is 1.5 MHz, and the ultrasonic power is 400 W to obtain a spray liquid. The spray liquid is sprayed on the surface of the composite film and cured to produce an anti-corrosion coating (coating thickness is 80±5 μm); the spraying pressure is 0.15 MPa, and the curing treatment is carried out at 55°C for 3 hours.
[0042] In the above embodiments and comparative examples: bisphenol A diglycidyl ether was purchased from Shanghai Yuanye Biotechnology Co., Ltd., item number: S27082; neopentyl glycol diglycidyl ether was purchased from Hubei Guangao Biotechnology Co., Ltd., item number: GA0318; n-decylamine was purchased from Hubei Guangao Biotechnology Co., Ltd., item number: GA2621; m-phenylenediamine was purchased from Hubei Guangao Biotechnology Co., Ltd.; N,N-dimethylformamide was purchased from Wuhan Kanosi Technology Co., Ltd., item number: 8598479; dichloromethane was purchased from Wuhan Kanosi Technology Co., Ltd.; polycaprolactone particles were purchased from Shanghai Yuanye Biotechnology Co., Ltd., item number: S26795; diatomaceous earth was purchased from Hubei Guangao Biotechnology Co., Ltd., item number: GA1883; tetraethyl silicate was purchased from Wuhan Kanos Technology Co., Ltd.; octadecyltrimethoxysilane was purchased from Hubei Guangao Biotechnology Co., Ltd., item number: GA7057; silicon carbide was purchased from Shanghai Yuanye Biotechnology Co., Ltd., item number: S46970; perfluorooctyltriethoxysilane was purchased from Shanghai Yuanye Biotechnology Co., Ltd., item number: S25162; epoxy resin was purchased from Yunsheng Chemical (Shandong) Co., Ltd.'s epoxy resin E44.
[0043] The brine chemical equipment with corrosion resistance in the comparative examples and embodiments of the present invention was tested and processed:
[0044] Q235 steel plates were used as brine chemical equipment, and anti-corrosion coatings were made on their surfaces to be used as samples for testing:
[0045] Water contact angle detection: The contact angle of the coating surface was measured using a contact angle meter (JC2000C1, Shanghai Zhongchen). Six different positions were taken for each sample and the average value was taken.
[0046] Wear resistance test: Place the coating surface of Q235 steel downward on a 600-grit sandpaper with a size of 25 cm × 20 cm (the contact area between the coating and the sandpaper is 8.4 cm 2 ), load a 100g weight on the sample, pull the sample at a speed of 5cm / s to move 25cm, and then pull it back in the opposite direction at the same speed. This is recorded as one wear cycle (50cm). After three wear cycles, replace new sandpaper and continue testing;
[0047] Corrosion resistance test: Different samples were immersed in 3.5% NaCl solution and electrochemical evaluation was performed at room temperature. The evaluation process was carried out using a P4000+ electrochemical station (Princeton); a three-electrode system was used, with a designated coated steel substrate as the working electrode, a carbon rod as the counter electrode, and a saturated Ag / AgCl electrode as the reference electrode; the area of the working electrode was 1.34 cm 2 The measurements were performed at open circuit potential over a frequency range of 10 -2 ~10 5 Hz, amplitude 10mV. The entire test process is carried out in a shielded box to protect it from interference from external electromagnetic fields and stray currents. To ensure repeatability, three parallel samples are prepared for each sample. The measured impedance data is fitted using ZSimpWin software to obtain the equivalent circuit and corresponding fitting data;
[0048] Scratch damage-healing: The anti-corrosion coating on the surface of the sample was scratched (the scratch depth was enough to expose the metal substrate), and then heated at 50°C for 2 hours to heal the scratches.
[0049] The results are shown in Table 1:
[0050] Table 1:
[0051]
[0052]
[0053] It can be seen from the above table that the brine chemical equipment with anti-corrosion function of the present invention has an anti-corrosion coating made on the inner wall of the brine chemical equipment, which can effectively carry out anti-corrosion treatment on the inner wall of the brine chemical equipment. At the same time, the super-hydrophobic property of the anti-corrosion coating can effectively prevent the brine from hanging on the inner wall of the brine chemical equipment during the processing, thereby further improving the anti-corrosion performance of the brine chemical equipment. At the same time, the anti-corrosion coating can be self-repaired and will not be damaged by the cleaning operation. The long-term effectiveness of the anti-corrosion and super-hydrophobic properties of the brine chemical equipment can be effectively guaranteed. Due to the super-hydrophobic property of the anti-corrosion coating, the cleaning effect of the inner wall of the brine chemical equipment can be effectively improved to avoid scaling and corrosion damage.
[0054] In the present invention, polycaprolactone nanofibers and epoxy-based shape memory polymer resins are combined by electrospinning technology to produce a composite film with self-repairing function, and the thermoplastic characteristics of the composite film can be used to give the super-hydrophobic coating a self-repairing function; the super-hydrophobic coating has excellent wear resistance; the coating has excellent anti-corrosion performance and long-term corrosion resistance; the coating has good self-repairing properties, and the coating still exhibits excellent corrosion resistance after repair;
[0055] An epoxy-based shape memory polymer (SMP) is coated on the surface of a metal substrate, and then combined with a polycaprolactone nanofiber membrane to obtain a composite membrane with a self-repairing function, and then octadecyltrimethoxysilane and perfluorooctyltriethoxysilane-modified diatomaceous earth particles and silicon carbide are combined on the surface of the composite membrane by air pressure spraying, and after curing, a super-hydrophobic anti-corrosion coating with a self-repairing function is obtained; the surface of the prepared super-hydrophobic anti-corrosion coating is relatively rough, with more papillae aggregated, and when a droplet contacts the coating, a layer of air holes is trapped in the micro-nano structure on the surface of the coating, and the coating and the droplet are separated by the air holes, which can effectively improve the super-hydrophobic performance of the anti-corrosion coating;
[0056] The surface of the polycaprolactone nanofiber membrane has abundant hydroxyl groups, which can chemically bond with the epoxy groups in the upper epoxy resin, so that the modified diatomaceous earth particles and silicon carbide can be firmly attached to the surface of the fiber membrane, thereby significantly improving the wear resistance and bonding strength of the particles; at the same time, the composite membrane composed of polycaprolactone nanofibers and the lower organic resin can achieve a strong bonding effect with the metal matrix through chemical bonding;
[0057] When heated above the glass transition temperature, the fixed switch segment of the epoxy shape memory polymer is reactivated and the entropy elastic behavior is restored, so that the deformed coating returns to the original chemical cross-linked state; after heat treatment, the composite film with self-healing function regains the flow state due to thermoplasticity, and the cracks at the damaged part can be repaired. When the temperature drops, the coating solidifies again, and the low surface energy of the repaired coating surface is not destroyed. At the same time, the micro-nano structure is restored. At this time, the rolling angle of the self-repaired coating surface is restored, and the super-hydrophobicity of the coating is restored. It can be seen that the self-healing effect of the coating surface morphology plays a vital role in the repair of its surface hydrophobicity.
[0058] When the super-hydrophobic coating is not damaged, the excellent hydrophobicity of the coating can reduce the contact time and contact area between the corrosive medium and the coating surface, thereby preventing the corrosive medium from penetrating into the coating. The coating as a whole still maintains integrity, so the corrosion resistance of the coating does not decrease with the extension of the solution immersion time; the super-hydrophobic coating has excellent and long-lasting corrosion resistance. After the coating is damaged, the damaged area can be completely repaired by heat treatment, thereby restoring its anti-corrosion performance; the heat-induced self-repairing function allows the damaged area to be well repaired, as well as the recovery of the air film in the convex structure of the super-hydrophobic surface;
[0059] Due to the air cushion and low surface energy between the surface structures of the anti-corrosion coating, the corrosion resistance can be significantly improved by preventing the penetration of corrosive liquids and limiting the formation of corrosion channels; at the same time, the self-healing property of the coating further improves the density of the coating; its repair mechanism is: when the external temperature is higher than the glass transition temperature of the composite fiber membrane, the molecular chains inside the resin are "activated", and driven by the internal stress, the composite fiber membrane begins to deform and flow, filling and repairing the damaged area, thereby restoring to the original morphology, and the protective performance of the coating is repaired again; this multiple rapid repair capability can meet the long-term durability requirements of superhydrophobic anti-corrosion coatings under common external damage;
[0060] In step one, bisphenol A diglycidyl ether, neopentyl glycol diglycidyl ether, toughening agent and curing agent A in the base material are blended and stirred evenly, and then poured and cured to prepare an epoxy shape memory polymer (SMP) on the inner wall surface of the brine chemical equipment to provide a supporting matrix for subsequent electrospinning fibers and ensure the self-repairing function of the composite membrane; in step two, polycaprolactone particles are dissolved in N, N-dimethylformamide and dichloromethane to prepare an electrospinning solution, and the electrospinning solution is electrospun on the surface of the epoxy shape memory polymer (SMP) to obtain a composite membrane with self-repairing function; in step three, diatomaceous earth and silicon carbide are added to anhydrous ethanol for ultrasonic treatment, so that the diatomaceous earth and silicon carbide are evenly dispersed in the anhydrous ethanol to ensure the uniformity of the subsequent reaction, tetraethyl silicate, octadecyl trimethoxysilane and perfluorooctyl triethoxysilane are added, and the treatment is stirred in a water bath, and octadecane Diatomaceous earth and silicon carbide are surface modified by trimethoxysilane and perfluorooctyl triethoxysilane, the siloxane group of perfluorooctyl triethoxysilane is hydrolyzed to generate silanol (Si—OH) group, and then oligosiloxane is generated through hydroxyl condensation reaction; the —OH group on the oligosiloxane reacts with the hydroxyl group adsorbed on the surface of silicon carbide to form hydrogen bonds, these hydrogen bonds are dehydrated during heating, and form Si—O—Si covalent bonds with silicon carbide, and the Si—O—Si covalent bonds effectively promote the adhesion between epoxy resin and silicon carbide particles, form a tight chemical interface layer, prevent the infiltration of water molecules, and further improve the superhydrophobic property of the coating; superhydrophobic modified particles, epoxy resin and meta-xylylenediamine are added to anhydrous ethanol for blending, spraying, curing, and preparing an anti-corrosion coating, and the addition of epoxy resin can fix the superhydrophobic modified particles well on the surface of the composite film, and the introduction of epoxy resin further improves the overall mechanical strength of the anti-corrosion coating.
[0061] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A brine chemical equipment with anti-corrosion function, characterized in that: The anti-corrosion coating is made on the inner wall of brine chemical equipment. The specific preparation steps are as follows: Step 1: pour and solidify the base layer on the inner wall surface of the brine chemical equipment; Step 2: electrospinning a composite membrane on the surface of a substrate by electrospinning a solution; Step 3: spray the spray liquid on the surface of the composite film, solidify it, and produce an anti-corrosion coating.
2. The brine chemical equipment with corrosion resistance according to claim 1 is characterized in that: The raw materials of the base layer include bisphenol A diglycidyl ether, neopentyl glycol diglycidyl ether, a toughening agent and a curing agent A, and the weight ratio of the bisphenol A diglycidyl ether, neopentyl glycol diglycidyl ether, the toughening agent and the curing agent A is 1: (0.09-0.11): (0.13-0.17): (0.2-0.3).
3. The brine chemical equipment with corrosion resistance according to claim 2 is characterized in that: The raw materials of the electrostatic spinning solution include polycaprolactone particles, N,N-dimethylformamide and dichloromethane, the volume ratio of N,N-dimethylformamide to dichloromethane is (2.8-3.2):1, and the mass fraction of polycaprolactone particles in the electrostatic spinning solution is 15.5-16.5%.
4. The brine chemical equipment with corrosion resistance according to claim 3 is characterized in that: The raw materials included in the spray liquid include diatomaceous earth, tetraethyl silicate, octadecyltrimethoxysilane, silicon carbide, perfluorooctyltriethoxysilane, epoxy resin and curing agent B; the weight ratio of the diatomaceous earth, tetraethyl silicate, octadecyltrimethoxysilane, silicon carbide and perfluorooctyltriethoxysilane is 1:(0.8-1.0):(0.6-0.7):(0.6-0.7):(0.1-0.2); the weight ratio of the total weight of the diatomaceous earth and silicon carbide to the epoxy resin is 1:(3.5-4.5); the weight ratio of the epoxy resin to the curing agent B is 1:(0.2-0.3).
5. The brine chemical equipment with corrosion resistance according to claim 4 is characterized in that: The weight ratio of bisphenol A diglycidyl ether, neopentyl glycol diglycidyl ether, toughening agent and curing agent A is 1:0.1:0.15:0.25; the volume ratio of N,N-dimethylformamide and dichloromethane is 3.0:1, and the mass fraction of polycaprolactone particles in the electrospinning solution is 16.0%; the weight ratio of diatomaceous earth, tetraethyl silicate, octadecyltrimethoxysilane, silicon carbide and perfluorooctyltriethoxysilane is 1:0.9:0.65:0.65:0.15; the weight ratio of the total weight of diatomaceous earth and silicon carbide to epoxy resin is 1:4.0; the weight ratio of epoxy resin and curing agent B is 1:0.
25.
6. The brine chemical equipment with corrosion resistance according to claim 4 is characterized in that: The toughening agent is one or more of n-octylamine, n-nonylamine, n-decylamine, n-dodecylamine and n-hexadecylamine; the curing agent A and curing agent B are one or more of ethylenediamine, hexamethylenediamine, diethylenetriamine, triethylenetetramine, diethylaminopropylamine, polyetheramine and m-xylylenediamine.
7. The method for producing brine chemical equipment with corrosion resistance according to claim 4, characterized in that: In step one, bisphenol A diglycidyl ether, neopentyl glycol diglycidyl ether, toughening agent and curing agent A in the base raw materials are mixed and stirred evenly, and then poured on the inner wall surface of the brine chemical equipment for curing treatment to prepare the base; during the curing process, it is first cured at 55-65° C. for 0.5-1.5 hours, and then cured at 90-100° C. for 1-2 hours.
8. The method for producing brine chemical equipment with corrosion resistance according to claim 7, characterized in that: In step 2, the polycaprolactone particles in the electrospinning liquid raw material are dissolved in N, N-dimethylformamide and dichloromethane to obtain an electrospinning liquid; the electrospinning liquid is electrospun on the surface of the base layer, and dried to produce a composite film; the electrospinning parameters are: voltage 13-17KV, receiving distance 12-18cm, spinning liquid flow rate 1.1-1.5ml / h; after electrospinning, it is dried at 40-50°C for 11-13h.
9. The method for producing brine chemical equipment with corrosion resistance according to claim 8, characterized in that: In step three, diatomaceous earth and silicon carbide in the coating liquid are added to anhydrous ethanol and ultrasonically treated for 10 to 20 minutes, and then tetraethyl silicate, octadecyltrimethoxysilane and perfluorooctyltriethoxysilane are added, stirred in a water bath for 11 to 13 hours, centrifuged, filtered, and dried to obtain super-hydrophobic modified particles; super-hydrophobic modified particles, epoxy resin and curing agent B are added to anhydrous ethanol, ultrasonically treated for 30 to 60 minutes to obtain a spray liquid, and the spray liquid is sprayed on the surface of the composite membrane , solidify to produce an anti-corrosion coating; the weight ratio of the total weight of diatomaceous earth and silicon carbide to anhydrous ethanol is 1:20-30, the water bath temperature is 40-50°C, and the stirring speed is 300-500r / min; the weight ratio of the epoxy resin to anhydrous ethanol is 1:4-6, the ultrasonic frequency is 1.5-1.7MHz, and the ultrasonic power is 400-600W; the spraying pressure is 0.15-0.25MPa, and the curing treatment is carried out at 55-65°C for 3-5 hours.
10. The method for producing brine chemical equipment with corrosion resistance according to claim 9, characterized in that: In step 1, during the curing process, the film is first cured at 60°C for 1.0 hour, and then cured at 95°C for 1.5 hours; In step 2, the electrospinning parameters are: voltage 15KV, receiving distance 15cm, spinning solution flow rate 1.3ml / h; drying at 45°C for 12h after electrospinning; in step 3, the weight ratio of the total weight of diatomaceous earth and silicon carbide to anhydrous ethanol is 1:25, the water bath temperature is 45°C, and the stirring speed is 400r / min; the weight ratio of the epoxy resin to anhydrous ethanol is 1:5, the ultrasonic frequency is 1.6MHz, and the ultrasonic power is 500W; the spraying pressure is 0.20MPa, and the curing treatment is carried out at 60°C for 4 hours.